Lamina Cribrosa and Choroid Features and Their Relationship to Stage of Pseudoexfoliation Glaucoma - Moghimi, Sasan (Invest Ophthalmol Vis Sci, 2018)
PURPOSE: To better understand the relationship of lamina cribrosa (LC) and choroid features to the severity of pseudoexfoliation glaucoma (PXG). METHODS: In this cross-sectional study, 137 eyes of 122 subjects (47 eyes with moderate/advanced PXG [mean deviation (MD), −15.0 ± 7.7 dB], 34 eyes with mild PXG [MD, −2.7 ± 1.5 dB], 32 aged-matched pseudoexfoliation syndrome [PXS] eyes, and 24 aged-matched control eyes) were investigated. Optic discs, LC thickness, and anterior LC depth (ALD; midsuperior, center, and midinferior) as well as peripapillary choroidal thickness were determined. Linear mixed modeling was used to adjust for age, sex, and axial length. RESULTS: A progressive decrease in LC thickness was found when comparing controls (271.9 ± 61.3 μm), PXS (212.6 ± 51.5 μm), mild PXG (180.8 ± 24.6 μm), and moderate/advance PXG (138.9 ± 37.5 μm) (P < 0.001). ALD was greater (P < 0.001) in moderate/advance glaucoma (306.7 ± 105.3 μm) and mild PXG (209.5 ± 79.7 μm) compared with PXS (155 ± 86.7 μm) and healthy controls (149.2 ± 103 μm). Although eyes with moderate/advance PXG had the thinnest choroid (117.2 ± 36.6 μm), choroidal thickness was comparable in mild PXG, PXS, and controls (150.0 ± 46.1, 159.7 ± 65.5, and 157.5 ± 51.1 μm, respectively; P = 0.002). Worse MD was the only factor associated with thinner LC (β = 2.344, P < 0.001) and choroid (β = 1.717, P = 0.009 μm) in PXG eyes. Higher IOP (β = 4.305, P = 0.013) and worse MD (β = −6.390, P < 0.001) were associated with deeper ALD in PXG. CONCLUSIONS: In pseudoexfoliation, LC thinning is an early sign, and there is progressive thinning with advancing glaucoma. Choroidal thinning is observable only with moderate/advanced glaucoma. In PXG eyes, LC thickness, depth, and peripapillary choroidal thickness are associated with glaucoma severity.